Mobile application with interactive maps based on the wayfinding design for public transport in the city of Saltillo, Coahuila - Olvera, Sandra (UNIVERSIDAD DE SONORA, 2022)
In the city of Saltillo, Coahuila, its inhabitants use public transport to a great extent to get around the city, however, there is no material to consult the routes of the transport routes. In consideration of this, this research proposed to determine the impact it causes on the inhabitants, the lack of an information system of public transport routes and, in what way the wayfinding design can contribute to the creation of a digital system that exceeds this difficulty. The results of the research expose the difficulties that the inhabitants have to know the routes covered by public transport and the urgent need to have an information instrument that provides the necessary information on the operation of public transport in the city. From this arises as a proposal, the development of a mobile application with interactive maps of the routes, schedules and reference points that allow the user to move within the city.